Development of Resilient Measurement Instruments for High School Students in Denpasar - Wilhelmina Olok; Nyoman Dantes; Ni Ketut Suarni (Bisma The Journal of Counseling, 2021)
The purpose of this development research is to determine the value of the validity and reliability of the tough character instrument. This study was designed with research and development methods. Analysis of the data used in the CVR and CVI tests from Lawshe, the empirical test with the product moment formula, while to test the reliability using Cronbach's alpha. The instrument validation test was carried out by experts. The results of data analysis using the Lawshe CVR test obtained an item value (CVR> 0), then the CVI value was obtained at 0.96, this value means that the content validity index of 45 items in the tough character instrument is very good. The results of the calculation of the validity of the item validity test using the Product Moment formula according to the valid category criteria. this shows that the level of reliability of the tough character instrument is very high, so this tough character instrument product is very important to be developed for students in high school.